How youth mentoring relationships end and why it matters: a mixed‐methods, multi‐informant study. Issue 1 (23rd December 2019) - Spencer, Renée; Keller, Thomas E.; Perry, Meghan; Drew, Alison L.; Clark‐Shim, Hyuny; Horn, John Paul; Miranda‐Díaz, Miriam; McCormack, Martha J.
Abstract: Scant empirical attention has been devoted to understanding endings in youth mentoring relationships, despite the frequency with which they occur. This study examined data from a mixed‐methods study of mentoring relationship endings in which youth mentees, the youth's parents or guardians, mentors, and program staff were surveyed about the closure process, and a subsample of program staff, mentors, and parents or guardians also participated in in‐depth qualitative interviews. Findings from a descriptive analysis detailing the perceptions of multiple stakeholders in the closure process as reported in surveys are presented along with case studies derived from a case‐based analysis of in‐depth qualitative interview data. Most relationship endings were initiated by the mentors, and although some matches engaged in an intentional and direct closure process, more often the endings were unclear or even confusing to program participants. Implications for practice are discussed, including recommendations for more training and greater involvement of program staff in the closure process, as are implications for future research.